2018
DOI: 10.1128/jvi.02064-17
|View full text |Cite
|
Sign up to set email alerts
|

The Unstructured Paramyxovirus Nucleocapsid Protein Tail Domain Modulates Viral Pathogenesis through Regulation of Transcriptase Activity

Abstract: The paramyxovirus replication machinery comprises the viral large (L) protein and phosphoprotein (P-protein) in addition to the nucleocapsid (N) protein, which encapsidates the single-stranded RNA genome. Common to paramyxovirus N proteins is a C-terminal tail (Ntail). The mechanistic role and relevance for virus replication of the structurally disordered central Ntail section are unknown. Focusing initially on members of the genus, a series of measles virus (MeV) and canine distemper virus (CDV) N proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
(92 reference statements)
3
25
0
Order By: Relevance
“…Interestingly, past experiments using mutations of N proteins of NiV cousins, canine distemper virus (CDV) and MeV, have shown that greater disorder at the N tail cause the viruses to be more virulent to ferrets in a laboratory [64]. While this was done experimentally using MeV and CDV in a laboratory setting, our results show for the first time that this also can be the case for NiV, but using an empirical analysis of NiV in the wild.…”
Section: Empirical Evidence Of a Correlation Between The Disorder Stamentioning
confidence: 53%
See 2 more Smart Citations
“…Interestingly, past experiments using mutations of N proteins of NiV cousins, canine distemper virus (CDV) and MeV, have shown that greater disorder at the N tail cause the viruses to be more virulent to ferrets in a laboratory [64]. While this was done experimentally using MeV and CDV in a laboratory setting, our results show for the first time that this also can be the case for NiV, but using an empirical analysis of NiV in the wild.…”
Section: Empirical Evidence Of a Correlation Between The Disorder Stamentioning
confidence: 53%
“…The N, P, and L proteins play important roles in the replication of the viral RNA [64,65]. The N protein when bound to the P protein, encapsidates the viral RNA during the replication of the latter.…”
Section: C-terminus Of N Protein Touches P Protein: the Focal Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrated that paramyxovirus polymerase bioactivity does not depend on the physical presence of the unstructured N-tail section. However, genetic evaluation of the N-tail truncated CDV revealed that robust virus growth coincided with the appearance of a mutation at residue 156 in N-core (15), implying that the deleted N-tail section may function as a long-range regulator of RdRP activity.…”
Section: Introductionmentioning
confidence: 99%
“…Another regulatory role may be contributed by the flexible Ntail region located at the Cterminus of the N protein. The N protein Ntail region has been shown both to be the site for P protein interaction 21,22 and to play a role in regulating transcriptional activity 23,24 . It is likely that this region is orientated toward the outside of the spiral 25 , allowing contact with the P protein.…”
Section: Discussionmentioning
confidence: 99%